Positive effect of lower body compression garments on subsequent 40 km cycling time trial performance - de Glanville, K. M.; Hamlin, M. J. (The Journal of Strength and Conditioning Research, 2012)
This study aimed to investigate the effect of wearing graduated compression garments during recovery on subsequent 40-km time trial performance. In a randomized single-blind crossover experiment, 14 trained multisport male athletes (mean ± SD: age 33.8 ± 6.8 years, 40-km time 66:11 ± 2:10 minutes:seconds) were given a graduated full-leg-length compressive garment (76% Meryl Elastane, 24% Lycra) or a similar-looking noncompressive placebo garment (92% Polyester, 8% Spandex) to wear continuously for 24 hours after performing an initial 40-km time trial in their normal cycling attire. After the 24-hour recovery period, the compression (or placebo) garments were removed, and a second 40-km time trial was then completed to gauge the effect of each garment on subsequent performance. One week later, the groups were reversed and testing procedures repeated. The participant's hydration status, nutritional intake, and training were similar before each set of trials. Performance time in the second time trial was substantially improved with compression compared with placebo garments (1.2 ± 0.4%, mean ± 90% confidence interval). This improvement resulted in a substantially higher average power output after wearing the compression garment compared with that after wearing the placebo garment (3.3 ± 1.1%). Differences in oxygen cost and rating of perceived exertion between groups were trivial or unclear. The wearing of graduated compressive garments during recovery is likely to be worthwhile and unlikely to be harmful for well-trained endurance athletes.